Character education strategies in improving students' spiritual intelligence - Suhifatullah, M. I.; Sutarman, Sutarman; Thoyib, Mastur (International research journal of management, IT and social sciences, 2021)
Education is an effort to foster student character. Purpose Want to know the character education management strategy in increasing the spiritual intelligence of students. The research method used qualitative instruments, namely (1). Focus (2). Observation and interviews (4) Data analysis collection. Conclusion: (1). Environmental observations at three schools have conducted a SWOT analysis (2). Formulation of a strategy regarding the vision and mission, based on the values of faith (3). Strategy implementation with intra and curricular based programs (4). Strategy evaluation serves to monitor learning (5). The learning strategy management process is very conducive. Implication (1). Strategic application has implications for the awareness of all school residents (2). The process of positive habituation has implications for school culture (3). The implementation of full-day school has implications for the creation of a school with character (4). Enforcement of discipline has implications for the commitment to school management.